Usefulness of Continuous Low-Dose Fentanyl in Combination with Dexmedetomidine and Midazolam for Intravenous Sedation: A Randomised Controlled Trial. (16th May 2022) - Okumura, Yoko; Sato (Boku), Aiji; Tachi, Naoko; Kanazawa, Mayuko; Kawabata, Miko; Okuda, Masahiro
Abstract : Intravenous dexmedetomidine (DEX) and midazolam (MZ) are currently used to achieve sedation in dental surgery under local anaesthesia. However, the efficacy of low-dose fentanyl (FEN) in combination with DEX and MZ sedation remains unclear. Therefore, we implemented a prospective randomised controlled trial to investigate the intra- and postoperative analgesic effects, intraoperative respiratory and circulatory dynamics, and frequency of intra- and postoperative adverse events of continuous low-dose fentanyl administration with DEX and MZ sedation. Patients aged 20–64 years scheduled for dental surgery under sedation were randomly assigned to the DEX+MZ (DM) or DEX+MZ+FEN (DMF) group. DEX was administered at 4  μ g/kg/h for 10 min and then reduced to 0.7  μ g/kg/h until the end of surgery. MZ was administered at 0.04 mg/kg upon the initial administration of DEX and 0.02 mg/kg every hour thereafter. In the DMF group, FEN infusion was administered at 2  μ g/kg/h during the initial administration of DEX and then reduced to 1  μ g/kg/h after 10 min until the end of surgery. Primary outcomes were intra- and postoperative analgesic efficacies, whereas secondary outcomes were intraoperative respiratory and circulatory dynamics. The total amount of intraoperative local anaesthetic administered and the heart rate were significantly lower in the DMF group than in the DM group (P = 0.044 and P < 0.01, respectively). No significant difference was observed in the frequency of postoperative administration of analgesics and intra- and postoperative adverse events. These findings demonstrated that low-dose FEN infusion in combination with DEX and MZ sedation in dental surgery provides intraoperative analgesia and suppresses tachycardia with little effect on blood pressure and respiratory dynamics and without effect on postoperative analgesia.